Resolution of the expert council “Relevant issues of iron deficiency in the Russian Federation” - O. M. Drapkina; A. I. Martynov; A. P. Baida; V. E. Balan; I. I. Baranov; E. E. Vlasova; P. A. Vorobiev; S. A. Volkova; I. Yu. Gaiduk; Zh. A. Gornostaeva; N. Yu. Grigorieva; Yu. E. Dobrokhotova; et al. (Кардиоваскулярная терапия и профилактика)
It is known that iron deficiency is a negative factor for the onset of pregnancy. It aggravates its course, increasing the risk of preeclampsia, placental insufficiency, uterine inertia, premature birth, bleeding and hypogalactia. This condition increases the risk of unfavorable outcomes, iron deficiency anemia and cognitive delay in a child. Raising the awareness of women of reproductive age and the clinical suspicion of physicians regarding the iron deficiency anemia and latent iron deficiency can facilitate timely visit a doctor. At the expert council “Relevant issues of iron deficiency in the Russian Federation” held in June 2020, aspects of the epidemiology, diagnosis and treatment of this condition were discussed, and promising directions for improving the situation were proposed.